The Influence of Ethanol Extract of Sambiloto Leaves and Sambung Nyawa Leaves To Decrease Concentration of Uric Acid - Suprijono, Agus; Selta Agatha Z, Vicky; Budi Utomo, Anang (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
Hyperuricemia is a condition of high concentration of uric acid in the blood that occurs because of a buildup of uric acid in the body. Uric acid is formed as a residue of the protein metabolism of foods containing purine. Some of the active compounds in the sambiloto leave (Andrographis Paniculata (Burm.F.) Nees) and sambung nyawa leave of allegedly being able to decrease the concentration of uric acid. The aims of this research is to know the influence of the difference between the ability of ethanol extract of sambiloto leaves and ethanol extract of sambung nyawa leaves (Gynura Procumbens (Lour.)Merr.) against the concentration of uric acid in vitro as well as know the effective concentration of ethanol extract of sambiloto leaves and extract ethanol of sambung nyawa leaves against a decrease in the concentration of uric acid in vitro. The extraction method used in this research is the method of extraction re-maceration by solvent ethanol 70% in 5 days, the sampling technique used was purposive sampling. The determination of concentration of uric acid is determined out by the Spectrophotometry method ABX Pentra. Series of concentrations used was 250, 500, 750, 1000, 1250, 1500, and 1750 ppm. The results of the research, the ability is effective in decreaced the concentration of uric acid in vitro on the extract of sambiloto leaves and extract of sambung nyawa leaves is 250 ppm. Statistical results showed that there is an influence of the ethanol extracts of sambiloto leaves and ethanol extracts of sambung nyawa leaves against decreasing the concentration of uric acid in vitro. And there is no difference between ethanol extracts of sambiloto leaves with ethanol extracts of sambung nyawa leaves against a decreased in the concentration of uric acid in vitro.